TLR4 gene polymorphism and milk traits in healthy and mastitis dairy cows - Lim, Su Ching (2015)
Bovine mastitis, an inflammatory disease of the mammary gland generally caused by intramammary infections, is the most frequently occurring disease in Malaysia dairy industry. During mastitis infection, cells of the innate immune system become activated through pattern recognition receptors that recognize conserved molecular signatures associated with the invading pathogen. Toll-like receptor 4 gene (Tlr4) is an important pattern recognition receptor that recognizes endotoxins associated with gram-negative bacterial infections. Its role in pathogen recognition and subsequent initiation of the inflammatory and immune response makes it a suitable candidate gene for enhanced mastitis resistance. There is limited molecular information on the Tlr4 single nucleotide polymorphisms (SNPs), especially for differentiation of mastitis resistance or susceptibility. This study was conducted to determine the DNA sequence variations of the Tlr4 of the mastitis and non-mastitis dairy cows. Milk was collected from 23 Friesian and 7 Friesian-Jersey crossbred lactating cows at the Redagri Farm, Linggi, Negeri Sembilan. Four of the Friesians suffered from mastitis. DNA was extracted from the milk samples and a region of Tlr4 was amplified using polymerase chain reaction (PCR) and the amplified DNA fragment sizes were estimated using gel electrophoresis. The somatic cell count (SCC), somatic cell score (SCS) and the composition traits of the milk were also determined. The PCR amplicons from two infected and two healthy samples were purified and sequenced and their associations with somatic cell score and milk composition traits were analyzed. The result showed that there was no significant variation in the PCR products from milk samples from the mastitis and non-mastitis cows; a single DNA band of 248 bp was exhibited. The sequence alignment of the purified PCR amplicons too showed 100% nucleotide similarity. There were no variations in the sequences of Tlr4 in mastitis and non-mastitis cows. Milk parameters recorded for mastitis and non mastitis animals were 14.72±2.17 vs. 8.86 ± 0.24 for SCS, 0.65±0.40 vs. 1.09±0.08 for milk fat percentage, 3.76±1.70 vs. 3.02±0.05 for protein percentage, 2.21±1.32 vs. 4.97±0.05 for lactose percentage, 6.42±2.14 vs. 8.59±0.08 for solid non-fat percentage and 7.21±2.42 vs. 9.68±0.12 for total solid percentage respectively. For all parameters there were no significant difference between the mastitis and non mastitis cows. The partial region of Tlr4 investigated in the present study may not be suitable to differentiate susceptibility of Friesian cows to mastitis. Other regions of the gene should also be investigated. The small number of mastitis animals in the study may also be the reason why SNPs in the Tlr4 region and differences in the milk parameters were not detected. A larger sample size of both healthy and mastitis animals should be investigated.